2014
DOI: 10.3171/2014.3.focus1429
|View full text |Cite
|
Sign up to set email alerts
|

An algorithmic strategy for selecting a surgical approach in cervical deformity correction

Abstract: Adult degenerative cervical kyphosis is a debilitating disease that often requires complex surgical management. Young spine surgeons, residents, and fellows are often confused as to which surgical approach to choose due to lack of experience, absence of a systematic method of surgical management, and today's plethora of information regarding surgical techniques. Although surgeons may be able to perform anterior, posterior, or combined (360°) approaches to the cervical spine, many struggle to rationally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(43 citation statements)
references
References 24 publications
0
43
0
Order By: Relevance
“…26 Not a few factors are considered to determine which of the approach is needed, including the location of compressive pathology, type, flexibility and location of the deformity. 27,28 There has been no clear goal of CL to be achieved in cervical deformity correction surgery. Similar to C7 SVA which is traditionally used to measure sagittal alignment of the thoracolumbar deformity, C2-7 SVA is acceptable in cervical deformity correction.…”
Section: Surgical Impact On Gsa Following Cervical Kyphosis Correctiomentioning
confidence: 99%
“…26 Not a few factors are considered to determine which of the approach is needed, including the location of compressive pathology, type, flexibility and location of the deformity. 27,28 There has been no clear goal of CL to be achieved in cervical deformity correction surgery. Similar to C7 SVA which is traditionally used to measure sagittal alignment of the thoracolumbar deformity, C2-7 SVA is acceptable in cervical deformity correction.…”
Section: Surgical Impact On Gsa Following Cervical Kyphosis Correctiomentioning
confidence: 99%
“…assessment of operative complication rates, and rigorous study of clinical outcomes after treatment. [8][9][10][11][12][13][14][15] Smith et al 16 recently reported substantial variability in the surgical planning for treatment of adult cervical deformities among a group of experienced spine surgeons from across North America. As a first step toward more structured study of ACD, Ames et al 17 recently proposed a standardized and easily reproducible classification system to assess cervical deformity within the framework of global spinopelvic alignment and clinically relevant parameters.…”
mentioning
confidence: 99%
“…10 Traditionally, the presence of any cervical kyphosis has been considered abnormal. However, this defi nition does not necessarily catch all subjects with CD.…”
Section: Radiological Measurementsmentioning
confidence: 99%